Preparation method of high-purity spheroidized nano titanium oxide
By using ternary polymer powder and sodium imidazolyl fluoroborate ionic liquid composite dispersant, the problem of spontaneous agglomeration of nanotitanium oxide is solved, and the preparation of high-purity spherical nanotitanium oxide is achieved, which improves the purity and morphological consistency of the product, and is suitable for photocatalytic and electronic devices.
Patent Information
- Application Number
- CN202510564940.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-07-11
AI Technical Summary
现有技术在制备纳米氧化钛时,分散剂不够稳定,导致纳米粒子自发团聚,纯度下降和形貌不规整,影响产品性能。
A composite dispersant based on ternary polymer powder and imidazolyl fluoroborate ionic liquid is used to prepare high-purity spherical nanotitanium oxide through electrostatic repulsion of sulfonic acid groups and template induction of ionic liquid, combined with the steric hindrance of the tertiary polymer, maintain the dispersion stability of the reaction system.
It improves the purity and morphological consistency of nanotitanium oxide, reduces the content of impurities, and ensures the stability of the product in photocatalytic and electronic devices.
Smart Images

Figure BDA0005385683330000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano-titanium oxide, and particularly relates to a method for preparing high-purity spherical nano-titanium oxide. Background Art
[0002] High-purity spherical nano-titanium oxide refers to titanium dioxide nanoparticles with a purity > 99.9%, a particle size range of 1 - 100 nm, and a regular spherical morphology. Its crystal structure is mainly anatase phase and rutile phase, or a composite structure of both. High-purity spherical nano-titanium dioxide has a high specific surface area, quantum size effect, and surface effect, which are beneficial to enhancing light absorption and reaction activity. Moreover, its low impurity content can ensure stability in applications such as photocatalysis and electronic devices.
[0003] When preparing nano-titanium dioxide by existing technologies, to solve the problem that nano-particles are prone to spontaneous aggregation, a dispersant generally needs to be added to maintain their dispersed state. Commonly used dispersants such as polyethylene glycol provide a repulsive effect through its long molecular chain to prevent aggregation. However, under certain synthesis conditions, due to the unstable properties of polymers such as polyethylene glycol, chain segment breakage may occur, resulting in the loss of the steric hindrance function and problems such as a decrease in the purity of the synthesized nano-titanium oxide and an irregular morphology. Summary of the Invention
[0004] The purpose of the present invention is to provide a method for preparing high-purity spherical nano-titanium oxide.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A method for preparing high-purity spherical nano-titanium oxide includes the following steps:
[0007] Step 1: Add a titanium salt, absolute ethanol, and deionized water into a reaction kettle, stir at 200 - 500 r / min for 5 - 10 min, then add a composite dispersant, continue stirring for 5 - 10 min, and then adjust the pH value of the system to 8.5 - 10 with a 20% sodium hydroxide solution. Stir and react at an internal pressure of 0.6 - 0.8 MPa and a temperature of 180 - 195 °C for 20 - 24 h. Naturally cool to room temperature and let it stand for 48 - 72 h. Centrifuge and filter, wash the precipitate with deionized water 2 - 3 times, and vacuum dry to constant weight to obtain hydrated nano-titanium oxide powder.
[0008] Step 2: Transfer the hydrated nano-titanium oxide powder to a muffle furnace, heat it to 800 - 950 °C at a rate of 3 - 5 °C / min and hold for 4 - 6 h. Naturally cool to room temperature and grind to obtain high-purity spherical nano-titanium oxide, thus completing the preparation method of high-purity spherical nano-titanium oxide.
[0009] Further, the dosage ratio of the titanium salt, absolute ethanol, deionized water and the composite dispersant is 1:10 - 15:10 - 15:0.01 - 0.05.
[0010] Further, the titanium salt is butyl carbonate or titanium tetrachloride.
[0011] Further, the composite dispersant is formed by mixing a ternary polymer powder and an imidazolium fluoroborate ionic liquid in a mass ratio of 1:1 - 3.
[0012] Further, the ternary polymer powder is prepared by the following steps:
[0013] Add styrene, sodium acrylsulfonate, methoxypolyethylene glycol methacrylate and isopropanol into a reaction kettle. Under the stirring speed of 200 - 300 r / min, at 65 - 70 °C and under nitrogen protection, dissolve benzoyl peroxide as an initiator with acetone and drop it into the reaction kettle. After the dropping is completed, keep the temperature at 80 - 85 °C for heat preservation reaction for 6 - 8 h, naturally cool to room temperature, adjust the pH value of the system to 6 - 7 with sodium hydroxide solution, remove the solvent by rotary evaporation, then disperse the remaining product in hydrochloric acid with a molar concentration of 0.1 mol / L with a mass 30 - 50 times that of the remaining product, stir at 25 - 30 °C for 7 - 8 h, centrifuge and wash 3 - 5 times, vacuum dry the precipitate, and grind to obtain the ternary polymer powder.
[0014] Further, the mass ratio of styrene, sodium acrylsulfonate, methoxypolyethylene glycol methacrylate and isopropanol is 3 - 3.4:4.5 - 4.8:45 - 48:35:1:20.
[0015] Further, the imidazolium fluoroborate ionic liquid is prepared by the following steps:
[0016] Step 1: Add 1 - vinylimidazole and n - hexyl bromide into a reaction kettle in a mass ratio of 1:1.8 - 2, stir and react at 70 - 75 °C and 200 - 300 r / min for 4.5 - 5 h, naturally cool to room temperature, filter, wash the filter cake with ethyl acetate 2 - 3 times, then recrystallize with anhydrous acetonitrile, and finally wash with ethyl acetate 2 - 3 times, vacuum dry to constant weight to obtain an ionic liquid intermediate.
[0017] Step 2: Add the ionic liquid intermediate, sodium tetrafluoroborate and methanol into a reaction kettle, stir at 20 - 25 °C and 500 - 800 r / min for 20 - 24 h, filter after standing for 1 - 2 h, distill off methanol under reduced pressure for the filtrate, then transfer the remaining liquid to chloroform with a volume 2 - 3 times that of the remaining liquid. After the mass of the precipitated solid remains unchanged, filter by suction, distill off chloroform under reduced pressure for the filtrate, and vacuum dry the remaining liquid to constant weight to obtain the imidazolium fluoroborate ionic liquid.
[0018] Further, the mass ratio of the ionic liquid intermediate, sodium tetrafluoroborate, and methanol is 2:1:10 - 12.
[0019] Advantages of the present invention:
[0020] In the preparation process of nano-titanium oxide of the present invention, a composite dispersant based on a ternary polymer powder and an imidazolium fluoroborate ionic liquid is added, and the process adaptability is better. The sulfonic acid group and imidazolium cation therein can remain stable at higher reaction temperatures and pH values, ensuring the dispersion stability of the reaction system, helping to improve the purity of the nano-titanium oxide product, with good product consistency and low impurity ion content.
[0021] The sulfonic acid group chelates metal ions to prevent impurity ions from incorporating into the lattice of titanium oxide, which helps to improve the purity of the nano-titanium oxide product. The imidazolium fluoroborate ionic liquid can accurately induce the growth of spherical nano-titanium oxide through a template effect. The composite dispersant system cooperates with the steric hindrance effect of the ternary polymer, the electrostatic repulsion effect of the sulfonic acid group, and the template induction effect of the ionic liquid to provide a stable process environment for the preparation of high-purity spherical nano-titanium oxide. Specific embodiments
[0022] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.
[0023] Example 1: This example provides a method for preparing high-purity spherical nano-titanium oxide, including the following steps:
[0024] S1: Add 3 kg of styrene, 4.5 kg of sodium acrylsulfonate, 45 kg of methoxypolyethylene glycol methacrylate, and 35 kg of isopropanol into a reaction kettle. Under a stirring speed of 200 r / min, at 65 °C and nitrogen protection, dissolve 1 kg of benzoyl peroxide as an initiator in 20 kg of acetone and drop it into the reaction kettle. After the dropping is completed, keep the reaction at 80 °C for 6 h, cool it naturally to room temperature, adjust the pH value of the system to 6 with sodium hydroxide solution, rotate and evaporate to remove the solvent, then disperse the remaining product in 30 times the mass of hydrochloric acid with a molar concentration of 0.1 mol / L, stir at 25 °C for 7 h, centrifuge and wash 3 times, and vacuum dry and grind the precipitate to obtain a ternary polymer powder.
[0025] S2: Add 1-vinylimidazole and n-hexyl bromide into a reaction kettle according to a mass ratio of 1:1.8, stir and react for 4.5 h under the conditions of 70 °C and 200 r / min, naturally cool to room temperature, filter, wash the filter cake twice with ethyl acetate, then recrystallize with anhydrous acetonitrile, finally wash twice with ethyl acetate, and vacuum dry to constant weight to obtain an ionic liquid intermediate.
[0026] S3: Add the ionic liquid intermediate, sodium tetrafluoroborate and methanol into a reaction kettle according to a mass ratio of 2:1:10, stir for 20 h under the conditions of 20 °C and 500 r / min, filter after standing for 1 h, distill off methanol under reduced pressure for the filtrate, then transfer the remaining liquid to chloroform with twice the volume, wait until the mass of the precipitated solid remains unchanged, carry out suction filtration, distill off chloroform under reduced pressure for the filtrate, and vacuum dry the remaining liquid to constant weight to obtain imidazolium sodium fluoroborate ionic liquid.
[0027] S4: Mix ternary polymer powder and imidazolium sodium fluoroborate ionic liquid according to a mass ratio of 1:1 to obtain a composite dispersant. Add 1 kg of tetrabutyl titanate, 10 kg of absolute ethanol and 10 kg of deionized water into a reaction kettle, stir at 200 r / min for 5 min, then add 10 g of the composite dispersant, continue to stir for 5 min, and then adjust the pH value of the system to 8.5 with a 20% sodium hydroxide solution. Stir and react for 20 h under the conditions of an autoclave pressure of 0.6 MPa and 180 °C, naturally cool to room temperature and stand for 48 h, carry out centrifugal filtration, wash the precipitate twice with deionized water, and vacuum dry to constant weight to obtain hydrated nano-titanium oxide powder.
[0028] S5: Transfer the hydrated nano-titanium oxide powder to a muffle furnace, heat it to 800 °C at a rate of 3 °C / min and hold for 4 h, naturally cool to room temperature, and grind to obtain high-purity spherical nano-titanium oxide, thus completing the preparation method of high-purity spherical nano-titanium oxide.
[0029] Example 2: This example provides a preparation method of high-purity spherical nano-titanium oxide, including the following steps:
[0030] S1: Add 3.2 kg of styrene, 4.65 kg of sodium allylsulfonate, 46.5 kg of methoxypolyethylene glycol methacrylate and 35 kg of isopropanol into a reaction kettle. Under the stirring speed of 250 r / min, at 67.5 °C and under nitrogen protection, dissolve 1 kg of benzoyl peroxide as an initiator with 20 kg of acetone and dropwise add it into the reaction kettle. After the dropping is completed, keep the temperature at 82.5 °C for 7 h for heat preservation reaction, then cool it naturally to room temperature, adjust the pH value of the system to 6.5 with sodium hydroxide solution, remove the solvent by rotary evaporation, and then disperse the remaining product in hydrochloric acid with a molar concentration of 0.1 mol / L and a mass 40 times that of the product, stir at 27.5 °C for 7.5 h, wash by centrifugation 4 times, vacuum dry the precipitate, and grind it to obtain the ternary polymer powder.
[0031] S2: Add 1-vinylimidazole and n-hexyl bromide into a reaction kettle according to the mass ratio of 1:1.9, stir and react at 72.5 °C and 250 r / min for 4.75 h, cool it naturally to room temperature, filter, wash the filter cake with ethyl acetate 2 times, then recrystallize with anhydrous acetonitrile, and finally wash with ethyl acetate 2 times, vacuum dry to constant weight to obtain the ionic liquid intermediate.
[0032] S3: Add the ionic liquid intermediate, sodium tetrafluoroborate and methanol into a reaction kettle according to the mass ratio of 2:1:11, stir at 22.5 °C and 650 r / min for 22 h, filter after standing for 1.5 h, distill off methanol under reduced pressure for the filtrate, then transfer the remaining liquid to chloroform with a volume 2.5 times that of the remaining liquid, filter by suction after the mass of the precipitated solid remains unchanged, distill off chloroform under reduced pressure for the filtrate, and vacuum dry the remaining liquid to constant weight to obtain imidazolium tetrafluoroborate ionic liquid.
[0033] S4: Mix the ternary polymer powder and imidazolium tetrafluoroborate ionic liquid according to the mass ratio of 1:2 to obtain a composite dispersant. Add 1 kg of titanium tetrachloride, 12.5 kg of absolute ethanol and 12.5 kg of deionized water into a reaction kettle, stir at 350 r / min for 7.5 min, then add 30 g of the composite dispersant, continue to stir for 7.5 min, and then adjust the pH value of the system to 9.5 with a sodium hydroxide solution with a mass fraction of 20%, stir and react at the kettle pressure of 0.7 MPa and 187.5 °C for 22 h, cool it naturally to room temperature and stand for 60 h, filter by centrifugation, wash the precipitate with deionized water 2 times, vacuum dry to constant weight to obtain hydrated nano-titanium oxide powder.
[0034] S5: Transfer the hydrated nano-titanium oxide powder to a muffle furnace, heat it up to 875 °C at a rate of 4 °C / min and keep it at this temperature for 5 h, then cool it naturally to room temperature, and grind it to obtain high-purity spherical nano-titanium oxide, thus completing the preparation method of high-purity spherical nano-titanium oxide.
[0035] Example 3: This example provides a method for preparing high-purity spherical nano titanium oxide, which includes the following steps:
[0036] S1: Add 3.4 kg of styrene, 4.8 kg of sodium allylsulfonate, 48 kg of methoxypolyethylene glycol methacrylate, and 35 kg of isopropanol into a reaction kettle. Under the stirring speed of 300 r / min, at 70 °C and under nitrogen protection, dissolve 1 kg of benzoyl peroxide as an initiator in 20 kg of acetone and drop it into the reaction kettle. After the dropping is completed, keep the temperature at 85 °C for 8 h of heat preservation reaction, naturally cool to room temperature, adjust the pH value of the system to 7 with sodium hydroxide solution, remove the solvent by rotary evaporation, then disperse the remaining product in 50 times the mass of hydrochloric acid with a molar concentration of 0.1 mol / L, stir at 30 °C for 8 h, centrifuge and wash 5 times, vacuum dry the precipitate, and grind it to obtain a ternary polymer powder.
[0037] S2: Add 1-vinylimidazole and n-hexyl bromide into a reaction kettle according to a mass ratio of 1:2, stir and react at 75 °C and 300 r / min for 5 h, naturally cool to room temperature, filter, wash the filter cake 3 times with ethyl acetate, then recrystallize with anhydrous acetonitrile, and finally wash 3 times with ethyl acetate, and vacuum dry to constant weight to obtain an ionic liquid intermediate.
[0038] S3: Add the ionic liquid intermediate, sodium tetrafluoroborate, and methanol into a reaction kettle according to a mass ratio of 2:1:12, stir at 25 °C and 800 r / min for 24 h, filter after standing for 2 h, distill off methanol under reduced pressure for the filtrate, then transfer the remaining liquid to 3 times the volume of chloroform. After the mass of the precipitated solid remains unchanged, filter by suction, distill off chloroform under reduced pressure for the filtrate, and vacuum dry the remaining liquid to constant weight to obtain imidazolium fluoroborate ionic liquid.
[0039] S4: Mix the ternary polymer powder and imidazolium fluoroborate ionic liquid according to a mass ratio of 1:3 to obtain a composite dispersant. Add 1 kg of titanium tetrachloride, 15 kg of absolute ethanol, and 15 kg of deionized water into a reaction kettle, stir at 500 r / min for 10 min, then add 50 g of the composite dispersant, continue to stir for 10 min, and then adjust the pH value of the system to 10 with a 20% sodium hydroxide solution by mass fraction. Stir and react at an internal pressure of 0.8 MPa and a temperature of 195 °C for 24 h, naturally cool to room temperature and stand for 72 h, centrifuge and filter, wash the precipitate 3 times with deionized water, and vacuum dry to constant weight to obtain hydrated nano titanium oxide powder.
[0040] S5: Transfer the hydrated nano titanium oxide powder to a muffle furnace, heat it to 950 °C at a rate of 5 °C / min and keep it at this temperature for 6 h, naturally cool to room temperature, and grind it to obtain high-purity spherical nano titanium oxide, thus completing the preparation method of high-purity spherical nano titanium oxide.
[0041] Comparative Example 1: On the basis of Example 3, in step S4, the imidazolium sodium fluoroborate ionic liquid in step S3 was directly used to replace the composite dispersant, and the remaining steps remained unchanged, to prepare high-purity spherical nano titanium oxide.
[0042] Comparative Example 2: On the basis of Example 3, in step S4, the ternary polymer powder in step S1 was directly used to replace the composite dispersant, and the remaining steps remained unchanged, to prepare high-purity spherical nano titanium oxide.
[0043] Comparative Example 3: On the basis of Example 3, in step S4, commercially available PEG 400 was directly used as the dispersant to replace the composite dispersant, and the remaining steps remained unchanged, to prepare high-purity spherical nano titanium oxide.
[0044] Perform physical characterization on the nano titanium oxide in Examples 1 - 3 and Comparative Examples 1 - 3, and the results are shown in Table 1:
[0045] Table 1
[0046]
[0047] As can be seen from Table 1, the nano titanium oxide prepared in Examples 1 - 3 is in a regular spherical shape, the particle size is small, the particle size distribution range is narrow, the consistency is good, and the content of impurity ions therein is also low.
[0048] The microscopic morphology of the nano titanium oxide prepared in Comparative Example 1 is not regular enough because the steric hindrance effect provided by the ternary polymer is lacking, resulting in the coexistence of rod-like structures and spherical structures, and the lack of the chelating effect of the sulfonic acid groups in the ternary polymer leads to an increase in the content of metal impurity sodium ions.
[0049] Agglomeration occurred in the nano titanium oxide prepared in Comparative Example 2, and the particle size distribution became wider, probably because the template guiding effect of the ionic liquid was lacking. The purity in Comparative Example 3 decreased significantly because only relying on the steric hindrance effect of the polyethylene glycol chain, the microscopic morphology of the production product cannot be directionally regulated, and under alkaline environment and high-temperature reaction conditions, the effect of PEG 400 as a dispersant will also decrease.
[0050] It should be noted that in this article, terms such as "including", "comprising" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0051] Although embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation method of high-purity spherical nano titanium oxide, characterized in that, It includes the following steps: Step 1: Add titanium salt, absolute ethanol and deionized water into a reaction kettle, stir at 200 - 500 r / min for 5 - 10 min, then add a composite dispersant, continue to stir for 5 - 10 min, and then adjust the pH value of the system to 8.5 - 10 with a 20% sodium hydroxide solution. Stir and react at an autoclave pressure of 0.6 - 0.8 MPa and a temperature of 180 - 195 °C for 20 - 24 h. Naturally cool to room temperature and stand for 48 - 72 h, centrifuge and filter, wash the precipitate with deionized water 2 - 3 times, and vacuum dry to constant weight to obtain hydrated nano titanium oxide powder; Step 2: Transfer the hydrated nano titanium oxide powder to a muffle furnace, heat it to 800 - 950 °C at a rate of 3 - 5 °C / min and hold for 4 - 6 h, naturally cool to room temperature, and grind to obtain high-purity spherical nano titanium oxide, thus completing the preparation method of high-purity spherical nano titanium oxide; The composite dispersant is composed of a ternary polymer powder and an imidazolium fluoroborate ionic liquid mixed in a mass ratio of 1:1 - 3.
2. The preparation method of a high-purity spherical nano titanium oxide according to claim 1, characterized in that, The dosage ratio of the titanium salt, absolute ethanol, deionized water and composite dispersant is 1:10 - 15:10 - 15:0.01 - 0.
05.
3. The preparation method of a high-purity spherical nano titanium oxide according to claim 1, characterized in that, The titanium salt is butyl carbonate or titanium tetrachloride.
4. The preparation method of a high-purity spherical nano titanium oxide according to claim 1, characterized in that, The ternary polymer powder is prepared through the following steps: Add styrene, sodium acrylsulfonate, methoxypolyethylene glycol methacrylate and isopropanol into a reaction kettle. Under a stirring speed of 200 - 300 r / min, at 65 - 70 °C and under nitrogen protection, dissolve benzoyl peroxide in acetone and drop it into the reaction kettle. After the dropping is completed, keep the temperature at 80 - 85 °C and hold for 6 - 8 h. Naturally cool to room temperature, adjust the pH value of the system to 6 - 7 with a sodium hydroxide solution, rotate and evaporate to remove the solvent, then disperse the remaining product in 30 - 50 times the mass of 0.1 mol / L hydrochloric acid, stir at 25 - 30 °C for 7 - 8 h, centrifuge and wash 3 - 5 times, vacuum dry the precipitate, and grind to obtain the ternary polymer powder.
5. The preparation method of a high-purity spherical nano titanium oxide according to claim 4, wherein, The mass ratio of styrene, sodium acrylsulfonate, methoxypolyethylene glycol methacrylate, isopropanol, benzoyl peroxide and acetone is 3 - 3.4:4.5 - 4.8:45 - 48:35:1:
20.
6. The preparation method of a high-purity spherical nano titanium oxide according to claim 1, characterized in that, The imidazolium fluoroborate ionic liquid is prepared through the following steps: Add an ionic liquid intermediate, sodium tetrafluoroborate and methanol into a reaction kettle, stir at 20 - 25 °C and 500 - 800 r / min for 20 - 24 h, stand for 1 - 2 h and then filter. Distill off methanol under reduced pressure from the filtrate, then transfer the remaining liquid to 2 - 3 times the volume of chloroform. After the solid precipitation mass remains unchanged, filter by suction, distill off chloroform under reduced pressure from the filtrate, and vacuum dry the remaining liquid to constant weight to obtain the imidazolium fluoroborate ionic liquid.
7. The preparation method of a high-purity spherical nano titanium oxide according to claim 6, characterized in that, The mass ratio of the ionic liquid intermediate, sodium tetrafluoroborate and methanol is 2:1:10 - 12.
8. The preparation method of a high-purity spherical nano titanium oxide according to claim 6, characterized in that, The ionic liquid intermediate is prepared through the following steps: Add 1-vinylimidazole and n-hexyl bromide into the reaction kettle, stir and react at 70 - 75 °C and 200 - 300 r / min for 4.5 - 5 h, naturally cool to room temperature, filter, wash the filter cake with ethyl acetate 2 - 3 times, then recrystallize with anhydrous acetonitrile, and finally wash with ethyl acetate 2 - 3 times, and dry to constant weight under vacuum to obtain the ionic liquid intermediate.
9. A method for preparing high-purity spherical nano titanium oxide according to claim 8, characterized in that, The mass ratio of the 1-vinylimidazole to the n-hexyl bromide is 1:1.8 - 2.